Penggunaan Singkatan dan Akronim dalam Percakapan Media Sosial - Achmad, Asmiranda; Alfira, Naila; Asdar, Nabila Khaufia Asdar (Pedagogical Education and Review of Linguistics, 2026)
This study aims to examine the use of abbreviations and acronyms in social media interactions and their implications for the development of the Indonesian language in the digital era. Employing a qualitative approach, this research applies content analysis to a selection of online news articles that reflect linguistic practices across various social media platforms, including Instagram, TikTok, X, and WhatsApp. The findings reveal a wide range of language shortening forms, encompassing common abbreviations, borrowed acronyms, and creative shortenings that emerge within digital communities. These forms of linguistic compression function as tools for communication efficiency, markers of group identity, and enhancers of informational authenticity in media presentations. Mass media plays a significant role in expanding and normalizing the use of digital terms, leading to their broader acceptance within society. However, the extensive use of language shortenings may also affect formal language proficiency and contribute to digital literacy gaps among certain social groups. Therefore, language shortening can be understood as a form of linguistic adaptation to the demands of rapid communication, globalization, and the evolving dynamics of digital culture. These findings underscore the importance of strengthening digital language literacy to ensure that language use remains appropriate to specific communication contexts.